Nitrogen fertilization enhances soil quality in the short-term in irrigated intensified maize systems - Victoria Lafuente; Ana Bielsa; María Alonso-Ayuso; Samuel Franco-Luesma; Carmen Castañeda; Laura B. Martínez-García; José L. Arrúe; Jorge Álvaro-Fuentes (Spanish Journal of Agricultural Research)
Aim of study: This study had a double objective that consisted of: (i) assessing the effects of N fertilisation on soil quality under different cropping systems (monocropping vs. double-annual cropping systems) under irrigated maize conditions; and (ii) identifying soil parameters related to soil quality that respond quickly to short-term management changes in Mediterranean irrigated maize systems.